Gold clusters showing pentagonal atomic arrays revealed by aberration-corrected scanning transmission electron microscopy - Mayoral, Alvaro (2010)
In this work we present the analysis by aberration corrected electron microscopy of the formation of gold clusters based on the proton irradiation of larger nanoparticles (NP). Pentagonal arrays have been observed and energetic calculations have been performed in order to prove the stability of these materials.